Implementing An Integrated In-Situ Coaching, Observational Audit, and Story-Telling Intervention to Support Safe Surgery. Issue 12 (December 2016) - Carthey, J; McCormack, K; Coombes, J; Gilbert, D; Farrar, D
This article describes an intervention that combined in-situ coaching, observational audits and story-telling to educate theatre teams at University College London Hospitals about the Five steps to safer surgery (NPSA 2010). Our philosophy was to educate theatre teams about 'what goes right' (good catches, exemplary leadership etc) as well as 'what could be improved'. Results showed improvements on 'behavioural reliability' metrics, a 68% increase in near miss reporting and a reduction in surgical harm incidents.